Kajian Tematik Tentang Bencana Angin dalam Al-Qur’an - Listiana Kartika Sari; Abdullah Mahmud (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In the Qur’an, the word “wind” is translated from the terms riḥ and riyaḥ. The main difference between these two terms lies in their connotations. Wind-related disasters can be caused by human disobedience to Allah’s commands, as seen in the story of the people of ‘Ad mentioned in Surah Al-Isra’ (68-69), which will be one of the verses discussed by the author along with several others. As Islam teaches its followers to reflect on the signs of Allah’s power, the author is interested in discussing the verses about wind-related disasters in the Qur’an from the perspectives of Tafsir Al-Misbah and Tafsir Al-Azhar.